The Dynamics of The Philippines Terrorism and Counter-Terrorism Policies in the Context of ASEAN Cooperation - Khoirul Umam; Mhd. Halkis; Susaningtyas Nefo Handayani Kertopati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Over the past two decades, ASEAN has grown as a breeding ground for the development of terrorist networks, both from the Middle East and those born within the ASEAN region. The Philippines, as one of the ASEAN member countries, is directly confronted with this threat. Using qualitative methods and a descriptive-analytic approach, this article discusses the dynamics of the threat in the Philippines by looking at the terrorism index, the growth of networks and attacks, and how the Philippines collaborates within the context of ASEAN to confront the threat. This paper concludes that the existing data shows that the dynamics of terrorism in the Philippines are on a relatively upward trend. In response, the Philippine government continues to develop its counter-terrorism policies by strengthening legal and regulatory aspects, establishing an authority to handle terrorism, and employing social approaches. In terms of cooperation, the Philippines is also striving to collaborate with fellow ASEAN member countries as well as countries outside the ASEAN region.